The ideology of Toba Batak in Dalihan Na Tolu: An Ecolinguistics Study (e-Journal of Linguistics, 2023)
This study is based on the structure of Dalihan na tolu which iscomposed of verb + verb in lines 1 and 2, and adverb + verb in line 3.These structures made Toba Batak people defined it in two ways;headed by somba, elek, and manat or headed by marhula-hula,marboru, and mardongan tubu. This study analyzed the valency andarguments in dalihan na tolu to define its real ideology. The findingsexplained (1) the three lines of dalihan na tolu are headed by the wordsof marhula-hula, marboru, and mardongan tubu, (2) while the way ofhow to apply the ideology is reflected from the words of somba, elek,and manat. These findings defined the real ideology of Toba Batak indalihan na tolu is to create and maintain relations; brothers to sistersand siblings in the way of somba (respected), elek (loved), and manat(maintain). Additionally, the way people of Toba Batak show theideology reflected in dalihan na tolu defined the ideology as anambivalent story that is half aligning with the real message of dalihanna tolu itself.
Keywords: Valency; arguments; dalihan na tolu; ideology; ecolinguistics